(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
Cervids and a moschid coming from various sites in the Baccinello-Cinigiano basin (Grosseto, Tuscany, Central Italy) are described. These remains have been recovered from levels correlatable with the horizon where the faunal assemblage known as V3 has been found. In the sedimentary succession within the Baccinello-Cinigiano basin, five successive faunal associations have been recognised. These assemblages document phases of population spanning the Late Miocene-Early Pliocene. The oldest assemblage, termed V0, is correlated with the MN11 "zone" (early Turolian), V1 and V2 assemblages with the MN12 "zone" (late Turolian), and V3 with the MN13 "zone" (late Turolian). Sediments bearing V3 assemblage are unconformably overlain by Lower Pliocene deposits containing remains of mammals referred to the early Villafranchian MN16a "zone". The cervid material studied here is referred to three taxa, Paracervulus cf. australis, Procapreolus cf. loczyi, Cervidae indet., and to a new representative of the family Moschidae Tuscomeryx huerzeleri (nov. gen., nov. sp.). Because of the occurrence of genus Paracervulus, the assemblage can be referred to a phase transitional between the Turolian and Ruscinian Mammal Ages of the biochronological continental scale.